Contribution Des Activites Artisanales Et Industrielles A La Degradation De L’environnement Urbain De Daloa - Zakilizou, Frederika Akissi N (European Scientific Journal, ESJ, 2016)
The Emergence of crafts, sector of informal activities in Côte d’Ivoire and especially in Daloa is the result of the inability of industrial units to revive the urban economy alone and absorb a large and cheap workforce. Crafts, composed of various activities, plays the role industry could not play. Therefore, these two important sectors for the urban economy of Daloa are complementary. However, their practice created inconvenience and have a negative effect on the city. These activities cause significant waste more or less toxic creating pollution problems and exposing actors to various risks. This study aims to show crafts and industry as sources of urban environment degradation spotlighting the products used in the operation of these activities as well as the inconvenience caused by employees.